1986
DOI: 10.1042/bj2330731
|View full text |Cite
|
Sign up to set email alerts
|

Protein conformation of potato (Solanum tuberosum) lectin determined by circular dichroism

Abstract: The structure of potato (Solanum tuberosum) lectin, which is a hydroxyproline-rich glycoprotein, has been investigated by circular dichroism. The spectra of the native lectin, and of the oxidized, reduced and carboxymethylated and deglycosylated derivatives were examined, as was a hydroxyproline-rich glycopeptide and its deglycosylated derivative. It is concluded that the lectin contains about 35% polyproline II conformation, 34% type II beta-turn and 31% irregular conformation. No indications were found for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Because of the presence of the extensin‐like domain interconnecting the two N‐ and C‐tandemly arrayed hevein‐like domains, the potato lectin adopts an unusual overall size and shape. Previous studies indicated that the hydroxyproline‐rich domain generated from the potato lectin adopts a polyproline type II helix (van Holst et al ., 1986). The 47 (hydroxy)Pro residues forming this extensin‐like domain are distributed in eight pseudo‐helical stretches as predicted on a molecular model built and minimized with insightii and discover 3 (result not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the presence of the extensin‐like domain interconnecting the two N‐ and C‐tandemly arrayed hevein‐like domains, the potato lectin adopts an unusual overall size and shape. Previous studies indicated that the hydroxyproline‐rich domain generated from the potato lectin adopts a polyproline type II helix (van Holst et al ., 1986). The 47 (hydroxy)Pro residues forming this extensin‐like domain are distributed in eight pseudo‐helical stretches as predicted on a molecular model built and minimized with insightii and discover 3 (result not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Conformational studies on the majority of glycosylated synthetic peptides have been performed by using CD in combination with other spectroscopic methods (see Section IV and Table VI). For CD spectroscopic studies on glycoproteins, see van Holst et al (1986) and Walsh eta!. (1990).…”
Section: {3 Turns In G/ycosylated Phosphorylated and Other Modifiedmentioning
confidence: 99%
“…Perczel et al (1992b). 'For the calculation of the percentages of ~Til, PPII, and irregular conformations, see van Holst et al (1986). studies, see Woody, 1985, andRose et al, 1985. ) The methods used to analyze the conformation and a brief conclusion are also given in Table VII. There are only a limited number of studies concerning the CD spectrum of tripeptides.…”
mentioning
confidence: 99%
“…The lectin module possesses a 13-turn secondary structure (Matsumoto eta/., 1983;van Hoist et al, 1986), and has a composition reminiscent of other plant chitinbinding proteins in that it is rich in cystine and glycine, contains tyrosine and tryptophan, and has no sugar (Allen et al, 1978;Chrispeels and Raikhel, 1991;Nagata and Burger, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the lectin domain, the HRGP domain of potato lectin is rich in hydroxyproline, is highly glycosylated with abundant arabinose and ~ minor amounts of galactose (Allen et a/., 1978), and has a polyproline-II secondary conformation (van Hoist et al, 1986). As such, the Hyp-rich domain compositionally resembles members of the extensin family which are frequently characterized by an extended polyproline-II secondary conformation (van Hoist and Varner, 1984;Lamport, 1977), and Ser-Hyp4 repetitive pentamers containing arabinosyloligosaccharides O-linked to Hyp, and monogalactosylserine (Kieliszewski and Lamport, 1994;Lamport, 1967Lamport, , 1969Lamport et aL, 1973).…”
Section: Introductionmentioning
confidence: 99%